A method for mandibular dental arch superimposition using 3D cone beam CT and orthodontic 3D digital model - Park, Tae-Joon (Korean Association of Orthodontists, 2012)
OBJECTIVE: The purpose of this study was to develop superimposition method on the lower arch using 3-dimensional (3D) cone beam computed tomography (CBCT) images and orthodontic 3D digital modeling. METHODS: Integrated 3D CBCT images were acquired by substituting the dental portion of 3D CBCT images with precise dental images of an orthodontic 3D digital model. Images were acquired before and after treatment. For the superimposition, 2 superimposition methods were designed. Surface superimposition was based on the basal bone structure of the mandible by surface-to-surface matching (best-fit method). Plane superimposition was based on anatomical structures (mental and lingual foramen). For the evaluation, 10 landmarks including teeth and anatomic structures were assigned, and 30 times of superimpositions and measurements were performed to determine the more reproducible and reliable method. RESULTS: All landmarks demonstrated that the surface superimposition method produced relatively more consistent coordinate values. The mean distances of measured landmarks values from the means were statistically significantly lower with the surface superimpositions method. CONCLUSIONS: Between the 2 superimposition methods designed for the evaluation of 3D changes in the lower arch, surface superimposition was the simpler, more reproducible, reliable method.